Anisotropic continuum damage model for prediction of failure in flax/polypropylene fabric composites. Issue 8 (29th April 2015) - Panamoottil, Shyam M.; Das, Raj; Jayaraman, Krishnan
Abstract : An anisotropic continuum damage modeling approach was applied to model failure of a composite of unidirectional flax in a polypropylene matrix under quasi‐static tensile loading. Tensile, compressive and shear stiffness, and strength values of the composite were characterized according to ASTM standards, and the damage was quantified by optical microscopy. Based on the experimental strength and damage values, an anisotropic strain‐dependent material damage model was developed and implemented in the finite element program ABAQUS. This was combined with geometric models of the fabric composites incorporating the yarn geometry. Good agreement was observed between the experimental and numerical stress–strain curves, and the failure strength prediction by the model was within 3.1% of the experimental value. This study shows that combining a geometric model closely incorporating the actual geometry of a fabric composite with an experimentally determined material degradation model can yield good predictions of the mechanical behaviour of the composite. POLYM. COMPOS., 37:2588–2597, 2016. © 2015 Society of Plastics Engineers